247 Swedish craft artists : a guide from south to north - Sarstad, Monika (Stockholm, Sweeden : Arvinius Forlag, 2008)
Featuring more than 600 full-color photographs, this book presents a comprehensive and insightful survey of the styles and trends of leading craftsmen and women in Sweden, showcasing their creativity and imagination in detail
Includes index
Keywords: Artisans -- Sweden -- Directories; Decorative arts -- Sweden -- Directories; Handicraft -- Sweden -- Directories